ChemInform Abstract: β‐Selective One‐Pot Fluorophosphorylation of D, D‐Heptosylglycals Mediated by Selectfluor. Issue 34 (August 2015) - Vincent, Stephane P.; Tikad, Abdellatif
Abstract A novel method for the fluorophosphorylation is applied to several heptose‐derived glycals.